Radiocapitellar plica: a narrative review - Colozza, Alessandra; Martini, Ilaria; Cavaciocchi, Michele; Menozzi, Margherita; Padovani, Sara; Belluati, Alberto (Acta Biomedica Atenei Parmensis, 2022)
Radiocapitellar plica is a vestigial lateral portion of elbow synovial fold which may cause pain and snap in some cases. Plica is a difficult and misleading diagnosis and it could be easily confused with a common lateral epicondylitis however, they are different conditions. Pathology full understanding and proper diagnosis is essential to achieve patient’s pain relief and functional recovery therefore, we reviewed the most relevant literature about radiocapitaller plica. The aim of this study is to provide the best and current concepts about: clinical evaluation, imaging findings and surgical treatments of radiocapitellar plica.